223k views
2 votes
Adding/Subtracting rational expressions

Adding/Subtracting rational expressions-example-1
User Sanghita
by
6.2k points

1 Answer

4 votes
7]
6/(x-1)-5x/4
subtracting the above we put the fraction under the same denominator:
6/(x-1)-5x/4
multiplying the denominators we get:
4(x-1)
thus subtracting we get:
6/(x-1)-5x/4
=(4*6-5x(x-1))/[4(x-1)]
=[24-5x^2+5x]/(4x-4)
Answer:
(-5x^2+5x+24)/(4x-4)


9]
3/(x+7)+4/(x-8)
the common denominator is:
(x+7)*(x-8)=(x+7)(x-8)
thus adding the fractions we put them under the same denominator as follows:
[3(x-8)+4(x+7)]/[(x+7)(x-8)]
=[3x-24+4x+28]/[(x+7)(x-8)]
=(7x+4)/[(x+7)(x-8)]

User Rallrall
by
6.1k points